Relevance of Character Education in Amanat Galunggung Manuscript with Unesco's Pillars of Education - Ranu Sudarmansyah; Farid Rizqi Maulana; Nur Syazwani Binti Mohd Shukri; Andika Rizki Nugraha; Syva Lestiyani Dewi (Universitas Muhammadiyah Mataram, 2024)
The degradation of moral values amid technological advancement during the 5.0 Industrial Revolution era and the complexities of the 21st century stand as a significant concern in contemporary education. Focused on UNESCO's four pillars and the cultural heritage embedded within the Amanat Galunggung manuscript, this study aims to unveil the contents of the Amanat Galunggung manuscript and explore their interrelation in shaping holistic individuals within modern education. Undertaking a crucial task, this research seeks to comprehend how these foundational aspects collectively combat the moral dilemmas arising from technological advancements in today's educational landscape. To interpret the contents of the Galunggung Amanat text, the hermeneutical method is used. Data was collected through documentation instruments and analyzed using content analysis techniques. The The results of the research show that the Amanat Galunggung text contains knowledge about self-introspection and how to behave, as well as recommendations for carrying out good actions and prohibitions against behaving not in accordance with the rules, especially in living together. This instills educational values which aim to develop individuals who are educated, skilled and have character. These values are in line with UNESCO's four pillars of education: learning to know, learning to do, learning to live together, and learning to be. The compatibility between the values in the Galunggung Mandate and the four pillars of UNESCO shows its potential as a solution for strengthening character amidst moral degradation in contemporary education.